Bibliometric study and visualization of myocardial infarction combined with heart failure, 1993–2023 - Wang, Kexin; Zhang, Shaoqiang; Zhu, Mingdan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe incidence of myocardial infarction has been rapidly increasing in recent years, making it one of the most common cardiovascular disorders. Due to the intricate interactions between large-vessel occlusions, microvascular dysfunction, ventricular remodeling, inflammation, and neurohormonal activation, patients who experience myocardial infarction are more likely to develop heart failure. Even though myocardial infarction and heart failure have been studied extensively, a thorough bibliometric analysis has not yet been carried out. The purpose of this study is to use bibliometric analysis to examine the trends in myocardial infarction linked to heart failure during the previous 30 years.MethodsFrom 1993 to 2023, this study methodically retrieved original publications from the Web of Science Core Collection (WoSCC) about myocardial infarction and heart failure. We identified research trends and hotspots in the subject by extracting and analyzing data on countries/regions, institutions, authors, journals, keywords, and references related to the issue using tools like CiteSpace and VOSviewer.ResultsOver the past 30 years, there has been a consistent increase in the number of published articles about myocardial infarction and heart failure, reaching a peak in 2022. The United States and China have a significant advantage in publication volume, each exceeding 200 articles. Brigham and Women's Hospital has published the most articles, totaling 49. In addition to publishing the most papers, the journal Circulation also had the biggest influence. The top five keywords include heart failure, myocardial infarction, mortality, acute myocardial infarction, and cardiovascular disease. In recent years, the outbreak words that have remained in the spotlight are management, association, risk, percutaneous coronary intervention, and guidelines.ConclusionOver the past 5 years, the increasing incidence of myocardial infarction accompanied by heart failure has garnered significant attention in research, leading to a substantial growth in related literature. The main goal of current research is to clarify the processes through which myocardial infarction causes heart failure; predictions and biomarkers are important areas of study. Future research is likely to concentrate on screening methods and treatment strategies.